Dragonfly‐Inspired Aerodynamics in Horizontal Axis Wind Turbines: Insights Into Fore‐Blade and Hind‐Blade Interaction Through Experimental and CFD Studies - Amr Khedr; Francesco Castellani (Wind Energy)
ABSTRACT Taking inspiration from dragonfly tandem wing aerodynamics, this study explores a novel wind turbine design featuring tandem blades. A 1‐m diameter horizontal axis wind turbine is tested in a wind tunnel at wind speeds between 4 and 12 m/s. In addition, computational fluid dynamics simulations validated with the experimental data further investigated the bioinspired configuration, also with the aid of flow visualization, and compared it to two conventional turbines designed from each blade of the bioinspired tandem blade configuration ensuring an equal solidity ratio for the three rotors. The results showed significant advantages for the tandem configuration at low tip speed ratios (TSRs) with an increase of up to 31% in torque generation compared to the sum of the individual blades, with no penalties at high TSRs. This improvement is attributed to the fore‐blade/hind‐blade interaction, with flow visualization showing a significant aerodynamic performance change with respect to the performance of the isolated individual blades at all TSRs. The presence of the hind blade significantly augments the performance of the fore blade by lowering the flow stagnation point, thus increasing the flow curvature, and also promoting better attachment by sucking the flow downward. Although the hind blade itself suffers from the fore‐blade wake, the tandem configuration showcased an overall enhancement in performance.